2021
DOI: 10.1002/asia.202100003
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of Nitriles, Esters, and Carbonates Catalyzed by Simple Earth‐Abundant Metal Triflate Salts

Abstract: During the past decade earth-abundant metals have become increasingly important in homogeneous catalysis. One of the reactions in which earth-abundant metals have found important applications is the hydroboration of unsaturated CÀ C and CÀ X bonds (X = O or N). Within these set of transformations, the hydroboration of challenging substrates such as nitriles, carbonates and esters still remain difficult and often relies on elaborate ligand designs and highly reactive catalysts (e. g., metal alkyls/hydrides). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 99 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Recently Fontaine, [21a] Ma, [21b] and Rueping's [21c] research groups demonstrated carbonate hydroboration using main group metal‐based compounds [21] . In 2021, Ruiter and coworkers reported the transition metal‐catalyzed hydroboration of carbonates [22] …”
Section: Resultsmentioning
confidence: 99%
“…Recently Fontaine, [21a] Ma, [21b] and Rueping's [21c] research groups demonstrated carbonate hydroboration using main group metal‐based compounds [21] . In 2021, Ruiter and coworkers reported the transition metal‐catalyzed hydroboration of carbonates [22] …”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the starting material remained stable with only a very small percentage of 4-propylguaiacol Our results indicate the formation of small amounts of byproduct 1 a under optimal conditions on 3 a are therefore likely the result of a Ni-catalyzed carbonyl hydroboration side reaction involving C=O rather than direct CÀ OAc bond cleavage, in accordance with recently reported transition metal-catalyzed hydroboration reactions of aryl acetates into alcohols. [27] The sterical nature of a t-Bu rationalizes why in esters the acetates are more prone to ArOH formation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there are a few reports on the hydroboration of carbonates (Scheme 1). 29,[31][32][33][34] Thus, it is crucial to develop hydroboration reactions of Al-catalyzed carbonates under mild conditions.…”
Section: Reduction Of Carbonatesmentioning
confidence: 99%